A Perturbed Postural Balance Test Using an Instrumented Treadmill – Precision and Accuracy of Belt Movement and Test-Retest Reliability of Balance Measures - Lesch, Kim J.; Lavikainen, Jere; Hyrylä, Vesa; Vartiainen, Paavo; Venojärvi, Mika; Karjalainen, Pasi A.; Tikkanen, Heikki; Stenroth, Lauri (Frontiers in Sports and Active Living, 2021)
A perturbed postural balance test can be used to investigate balance control under mechanical disturbances. The test is typically performed using purpose-built movable force plates. As instrumented treadmills become increasingly common in biomechanics laboratories as well as in clinical settings, these devices could be potentially used to assess as well as train balance control. The purpose of the study was to investigate how an instrumented treadmill applies to the perturbed postural balance test. This was investigated by assessing the precision and reliability of the treadmill belt movement and the test-retest reliability of the perturbed postural balance test over five days. Postural balance variables were calculated from the center of pressure trajectory and included peak displacement, time to peak displacement, and recovery displacement. Additionally, the study investigated short-term learning effects over five days. Eight healthy participants (age 24-43 y) were assessed on five consecutive days with four different perturbation protocols. Center of pressure data was collected using the force plates of the treadmill while participant and belt movement was measured with an optical motion capture system. The results showed that the treadmill can reliably deliver the intend-ed perturbations with less than 1% deviation in the total displacement and with minimal variability between days and participants (typical errors 0.06-2.71%). However, the treadmill was not able to reach the programmed 4 m/s2 acceleration, reaching only about 75% of it. Test-retest reliability in the selected postural balance variables ranged from poor to good (ICC 0.156-0.752) with typical errors between 4.28-28.22%. Learning effects were detected based on linear or quadratic trends (p<0.05) in peak displacement of the slow forward and fast backward protocols and in time to peak displacement in slow and fast backward protocols. The participants altered the initial location of the center of pressure relative to the foot depending on the direction of the perturbation. In conclusion, the precision and accuracy of belt movement were found to be excellent. Test-retest reliability of the balance test utilizing an instrumented treadmill ranged from poor to good which is in line with previous investigations using purpose-built devices for perturbed postural balance assessment.